PENGARUH TERPAAN FILM DOKUMENTER DIRTY VOTE TERHADAP OPINI PENGGUNA TWITTER PADA MASA TENANG PEMILU - Wina Puspita Sari; Muria Putriana; Raisa Firstia; Bintang Fauzan; Farras Amin Abdillah; Dewi Rangganis Hadi Arum Ningrum; Risky Akbar Sunaryo; Rangga Audy Islamy; Akbar Sunaryo, Risky (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
The movie Dirty Vote highlights the sensitive issue of fraud and abuse of power in the context of elections. The influence of its content was seen through the diverse opinions that developed on Twitter, with some users expressing disappointment with the portrayal of fraud revealed in the movie, while others appreciated the transparency efforts in exposing the alleged abuse of power. The purpose of this study was to determine the extent to which the Dirty Vote movie influenced the opinions of candidate voters. The research method used is descriptive quantitative. The population in this study were Twitter users who watched the Dirty Vote movie as many as 276,965 people and a sample of 100 respondents with the sampling technique used was a non-probability sampling technique, namely accidental sampling. The results of the correlation test using SPSS show that Media Exposure has a very strong effect on Public Opinion with a correlation value of 0.944 with a coefficient of determination of 0.944 indicating that 94.4% of the Public Opinion variable is influenced by Media Exposure, while the rest is influenced by other factors.